Proximal, Microbiological and Nutritional Characterization in Chinese Potato Flour of the White Variety Colocasia Esculenta for Application in Functional Foods - F. López; L. Arboleda; V. González (ESPOCH Congresses)
The study presents a qualitative-quantitative scope through descriptive statistics for the variables studied with its analyses, with the objective of performing physical, proximal, microbiological and contained characterization of amino acids in Chinese potato flour of the white variety Colocasia esculenta for its application in functional foods. By obtaining the flour, the proximal percentages are evaluated; moisture 9.01%, ash 2.24 ± 0.15% protein 2.02 ± 0.02% fiber 4.25 ± 0.26% and fat 0.43 ± 0.15%. Additionally, the physical-chemical analyses carried out on the flour obtain a pH of 6.66 ± 0.10% acidity (oxalic) 2.24 ± 0.00% Brix degrees 2 ± 0.50%. The nutritional values reported in the Chinese potato flour of the white variety lies mainly in its content of Methionine with a value of 21.15%, Alanine with 10.43%, Isoleucine with 8.08%, Threonine with 7.41%, Histidine with 3.65% and lysine with 3.10%. Finally, the microbiological analysis of the product is determined, concluding that they are within the parameters established in wheat flours with the INEN 616: 2006 standard; thus it is considered of good quality, suitable for human consumption and consequently, for use in the food industry. Therefore, it can be used as functional food or be transformed through the use of different techniques, thus being an important plant genetic resource to improve the nutritional quality of food, productivity, food health, as well as the protection and prevention of diseases in areas of the equator with high levels of malnutrition.